2017
DOI: 10.3390/ma10090993
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Performance of Ti-6Al-4V Additively Manufactured Specimens with Integrated Capillaries of an Embedded Structural Health Monitoring System

Abstract: Additive manufacturing (AM) of metals offers new possibilities for the production of complex structures. Up to now, investigations on the mechanical response of AM metallic parts show a significant spread and unexpected failures cannot be excluded. In this work, we focus on the detection of fatigue cracks through the integration of a Structural Health Monitoring (SHM) system in Ti-6Al-4V specimens. The working principle of the presented system is based on the integration of small capillaries that are capable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Fatigue failure occurred at a load level of 818 MPa in the HIPped specimen without chemical etching (Specimen 1). As compared to previous tests, this result equals the benchmark of wrought Ti-6Al-4V specimens [5,6] as well as the stress relieved specimen produced using laser based PBF [6] and clearly outperforms all specimens tested under as-built conditions [6]. It is clear that HIP has certainly improved the fatigue performance, but fatigue initiation eventually occurred at the capillary surface.…”
Section: Fatigue Failure and Fracture Surface Analysissupporting
confidence: 58%
See 2 more Smart Citations
“…Fatigue failure occurred at a load level of 818 MPa in the HIPped specimen without chemical etching (Specimen 1). As compared to previous tests, this result equals the benchmark of wrought Ti-6Al-4V specimens [5,6] as well as the stress relieved specimen produced using laser based PBF [6] and clearly outperforms all specimens tested under as-built conditions [6]. It is clear that HIP has certainly improved the fatigue performance, but fatigue initiation eventually occurred at the capillary surface.…”
Section: Fatigue Failure and Fracture Surface Analysissupporting
confidence: 58%
“…The step method was used to accelerate testing, with a run-out 500,000 cycles in each step. The initial stress level was 114 MPa, well below the expected fatigue strength [5,6], and increased with 78.1 MPa in each step. The test frequency was 15 Hz and a stress ratio (R ratio) of 0.1 was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the capillary does not act as an initiation site for fatigue damage and that the fatigue properties of the specimen remain unaltered when including such capillaries [29,30]. A summary of fatigue tests of specimen with and without capillary is shown in table 1 in [31].…”
Section: Materials and Experimental Set-upmentioning
confidence: 99%
“…The fatigue performance was greatly reduced when considering a printed capillary. It is concluded that the surface quality of the integrated capillary is of primary importance in order not to influence the structural integrity of the component to be monitored [14,15].…”
Section: Lesson Learned From Fatigue Tests Of Eshm Systemmentioning
confidence: 99%